Understanding the bonding mechanisms of directly sputtered copper thin film on an alumina substrate - Lim, Ju Dy (2017)
The evaluation of bonding mechanisms between magnetron sputtered copper (Cu) thin films and a ceramic substrate was carried out using polycrystalline and monocrystalline alumina (Al2O3) substrates with different surface roughness. Three different bonding mechanisms, viz., surface adsorption, mechanical interlocking, and diffusion bonding have been assessed. A tensile test was applied to measure the interfacial adhesion strength between the Cu films and the Al2O3 substrate. The contribution to the interfacial adhesion from each of the bonding mechanisms was elucidated based on the adhesion strength. Without special surface pre-treatment, physical adsorption is the main factor for the film adhesion, contributing ~ 5.9 MPa adhesion strength between this directly sputtered Cu film and a flat Al2O3 substrate. For substrates with surface roughness around 350–500 nm, mechanical interlocking enhances the film adhesion up to 18.6% compared to the flat surface. Post-deposition annealing at 300 °C has increased adhesion strength by 18%, and diffusion bonding may be operative.